1984
DOI: 10.1111/j.1939-0025.1984.tb01529.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood social adjustment, adolescent status, and young adult mental health.

Abstract: A sample of 2453 grade school children were followed through record sources into young adulthood. Data on peer status and social class were collected, and a subset was subsequently located in high school yearbooks. Those with mental health treatment during young adulthood were determined. Significant relationships were found between peer status and high school activity, and young adult adjustment, with low peer status children having two to three times greater risk for mental health treatment contact in young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
3

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 8 publications
1
10
1
3
Order By: Relevance
“…Although the literature was replete with studies proving the predictability of low peer status for later problems, especially delinquent or criminal behavior and emotional problems, based on observations by adults or sociometric choices by peers (Cowen et al, 1973;Kupersmidt & Coie, 1990;Parker & Asher, 1987;Roff & Wirt, 1984b), this study did not corroborate those findings with self-perceived unpopularity. Also, there was no significant link between academic performance and early self-perceived unpopularity.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Although the literature was replete with studies proving the predictability of low peer status for later problems, especially delinquent or criminal behavior and emotional problems, based on observations by adults or sociometric choices by peers (Cowen et al, 1973;Kupersmidt & Coie, 1990;Parker & Asher, 1987;Roff & Wirt, 1984b), this study did not corroborate those findings with self-perceived unpopularity. Also, there was no significant link between academic performance and early self-perceived unpopularity.…”
Section: Discussioncontrasting
confidence: 55%
“…Other poor outcomes in later life found to be associated with earlier unpopularity were poor academic achievement (Chance, 1989;Parker & Asher, 1987;Roff & Wirt, 1984b), psychosis (Fleming & Ricks, 1970;Roff, 1963), neurosis (Robins, 1966), and criminal behavior (Chance, 1989;Parker & Asher, 1987;Roff et al, 1972).…”
Section: Peer Status Related To Poor Functioningmentioning
confidence: 99%
“…Longitudinal studies have also pointed to the importance of peer status for later depressive symptoms (Boivin et al 1995a;Nolan et al 2003;Vernberg 1990) and anxiety disorders (Bell-Dolan et al 1995;Strauss et al 1988) in children and adolescents. There is much less evidence regarding effects at later ages, but at least two studies have used register data to follow children up into young adulthood (Cowen et al 1973;Roff and Wirt 1984). Both studies found that children with low peer ratings were at increased risk of mental health problems ten or more years later.…”
Section: Longitudinal Psychiatric Implications Of Peer Statusmentioning
confidence: 95%
“…Les questions mises en jeu dans les amitiés à l'adolescence ont un impact sur la santé mentale. Quelques recherches (RoIf, 1976 ;Roff et Wirt, 1984) ont pu démon-trer que l'absence d'amitié à l'adolescence constituait un prédicteur d'ajustement personnel problématique à l'âge adulte et que l'absence de liens d'intimité avec les pairs avait une incidence sur la santé mentale. Des recherches rétrospectives sur la schizophrénie ont également fait ressortir que l'absence d'amitié à l'adolescence devait être considérée comme un élé-ment majeur dans l'étiologie de cette maladie mentale (Riesman, 1984).…”
Section: Les Fonctions Des Amitiés Adolescentesunclassified